Taphonomy of the Ediacaran Fossil Pteridinium Simplex Preserved Three-Dimensionally in Mass Flow Deposits, Nama Group, Namibia. (March 2014) - Meyer, Mike; Elliott, David; Schiffbauer, James D.; Hall, Michael; Hoffman, Karl H.; Schneider, Gabi; Vickers-Rich, Patricia; Xiao, Shuhai
Abstract : Ediacara-type fossils are found in a diverse array of preservational styles, implying that multiple taphonomic mechanisms might have been responsible for their preservational expression. For many Ediacara fossils, the "death mask" model has been invoked as the primary taphonomic pathway. The key to this preservational regime is the replication or sealing of sediments around the degrading organisms by microbially induced precipitation of authigenic pyrite, leading toward fossil preservation along bedding planes. Nama-style preservation, on the other hand, captures Ediacaran organisms as molds and three-dimensional casts within coarse-grained mass flow beds, and has been previously regarded as showing little or no evidence of a microbial preservational influence. To further understand these two seemingly distinct taphonomic pathways, we investigated the three-dimensionally preserved Ediacaran fossil Pteridinium simplex from mass flow deposits of the upper Kliphoek Member, Dabis Formation, Kuibis Subgroup, southern Namibia. Our analysis, using a combination of petrographic and micro-analytical methods, shows that Pteridinium simplex vanes are replicated with minor pyrite, but are most often represented by open voids that can be filled with secondary carbonate material; clay minerals are also found in association with the vanes, but their origin remains unresolved. The scarcity of pyrite and the development of voids are likely related to oxidative weathering and it is possible that microbial activities and authigenic pyrite may have contributed to the preservation of Pteridinium simplex ; however, any microbes growing on P. simplex vanes within mass flow deposits were unlikely to have formed thick mats as envisioned in the death mask model. Differential weathering of replicating minerals and precipitation of secondary minerals greatly facilitate fossil collection and morphological characterization by allowing Pteridinium simplex vanes to be parted from the massive hosting sandstone.